2020
DOI: 10.33225/jbse/20.19.824
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Approach of Response Pattern of Diagnostic Test Items in Evaluating Students’ Conceptual Understanding of Characteristics of Particle of Matter

Abstract: This research aimed to evaluate the students’ conceptual understanding and to diagnose the students’ preconceptions in elaborating the particle characteristics of matter by development of diagnostic instrument as well as Rasch model response pattern analysis approach. Data were acquired by 25 multiple-choice written test items distributed to 987 students in North Sulawesi, Indonesia. Analysis on diagnostic test items response pattern was conducted in three steps: 1) conversion of raw score to a homogenous inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Good questions will be considered the same, both for men and women, from the aspect of the level of difficulty of the questions. In this study, the results of the DIF analysis showed that, in general there were no different levels of difficulty based on gender differences (male and female), as seen from the probability value greater than 0.05 (Figure 5) (Chan et al 2020;Laliyo et al 2020). A probability value greater than 0.05 indicates that there is no bias on the items based on gender differences or DIF.…”
Section: Analysis Differential Item Functioning (Dif)mentioning
confidence: 48%
“…Good questions will be considered the same, both for men and women, from the aspect of the level of difficulty of the questions. In this study, the results of the DIF analysis showed that, in general there were no different levels of difficulty based on gender differences (male and female), as seen from the probability value greater than 0.05 (Figure 5) (Chan et al 2020;Laliyo et al 2020). A probability value greater than 0.05 indicates that there is no bias on the items based on gender differences or DIF.…”
Section: Analysis Differential Item Functioning (Dif)mentioning
confidence: 48%
“…ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ Item 2 was with somewhat higher OUTFIT mean square, suggesting less accurate predictions of these items. Even though not all items meet all the criteria, the quality of the items is not affected (Laliyo et al, 2020). The item fit statistics showed that most items were not deviant, valid, and appropriate.…”
Section: Validity: Fit Statistics and Wright Mapmentioning
confidence: 97%
“…This finding is further backed by Adadan and Ataman [55] who argued that particulate nature of matter (PNM) is one of the foundational concepts that promote, shape, and constrain the understanding of subsequent concepts in science, particularly in chemistry. However, the fact that conceptual understanding of the topic has been described to be difficult considering the abstract nature of the concept [13]. In addition, the continued low students' achievements, because of ineffective instructional approach adapted by the science teachers [20,56], necessitate the quest for further investigation into basic science instruction.…”
Section: Student's Misconception On States Of Mattermentioning
confidence: 99%
“…The author further suggested that more studies on methods to reduce or eliminate such misconceptions should be conducted. Laliyo et al [13] also argued that more studies should be conducted because some studies have found students' misconception of the states of matter to persist as they progress further. Hanson [14] argued that because of the lingering misconceptions that students hold coupled with low academic achievement, invariably, lead to loss of interest in studying science; thus, teachers should select and adopt instructional approach that investigate prior information of students, provides hands and mind on activities that support science teachers in dissemination of knowledge through inquiry activities.…”
Section: Introductionmentioning
confidence: 99%